2022
DOI: 10.1101/2022.07.19.500697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitotic clustering of pulverized chromosomes from micronuclei

Abstract: Complex genome rearrangements can be generated by the catastrophic shattering of mis-segregated chromosomes trapped within micronuclei through a process known as chromothripsis. Since each chromosome harbors a single centromere, how acentric fragments derived from shattered chromosomes are inherited between daughter cells during mitosis remains unknown. Here we tracked micronucleated chromosomes by live-cell imaging and show that acentric fragments cluster in close spatial proximity throughout mitosis for bias… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Chromothripsis ( cth ) is a phenomenon by which hundreds of rearrangements originate through random shattering and reshuffling of clustered chromosome regions within a single catastrophic event. The predominant method of reassembly of the shattered pieces is classical non-homologous end joining (C-NHEJ) [6‒8]. ogm (2p)cth…”
Section: Resultsmentioning
confidence: 99%
“…Chromothripsis ( cth ) is a phenomenon by which hundreds of rearrangements originate through random shattering and reshuffling of clustered chromosome regions within a single catastrophic event. The predominant method of reassembly of the shattered pieces is classical non-homologous end joining (C-NHEJ) [6‒8]. ogm (2p)cth…”
Section: Resultsmentioning
confidence: 99%
“…One feature that contributes to hotspots of HPV DNA integration are common and cell‐type specific chromosomal fragile sites, which can develop DBS during replication stress which also can lead to alteration in gene expression levels 20,82–84 . Recent studies have also found that HPV integration can occur at DBS associated with chromothripsis, which as previously mentioned can generate genome‐wide chromosomal changes and have MHS at repair junctions 85–88 . Integration next to coding regions or even distant flanking regions of genes can lead to changes like amplification, rearrangement, translocation, or long‐range cis interactions.…”
Section: Mechanisms Of Microhomology‐mediated Dna Repair Machinery In...mentioning
confidence: 99%
“…TopBP1 is an active protein during mitosis and is critical for maintaining genome integrity (16,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). The ability of E2-K111Q to remove TopBP1 from mitotic chromatin indicated this protein may disrupt mitosis.…”
Section: Lysine Mutations In E2 Disrupt E2 Mitotic Interaction and Ab...mentioning
confidence: 99%